2021
DOI: 10.14740/wjon1392
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Profile of Breast Carcinoma Using Immunohistochemistry Markers in Mexican Women

Abstract: Background: In Mexico, breast cancer is the leading cause of death by malignant tumors in women aged 20 and older. The World Health Organization estimates that 69% of deaths caused by breast cancer occur in developing countries. Little is known about the prevalence of breast carcinoma in Mexico and its molecular subclassification.Methods: This retrospective cross-sectional study included patients who underwent a mastectomy (single, radical or lumpectomy) or a breast tumor biopsy (core-needle or excisional) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The results from a retrospective and crosssectional study of 379 BC patients at a mean age of 54.63 years (range, 23-89 years) in Mexico indicate luminal B subtype in 143 (in 37.73%), luminal A subtype in 139 (in 36.67%), TNBC in 65 (in 17.15%), and HER2 (+) in 32 patients (in 8.44% of the cases) [15].…”
Section: Discussionmentioning
confidence: 99%
“…The results from a retrospective and crosssectional study of 379 BC patients at a mean age of 54.63 years (range, 23-89 years) in Mexico indicate luminal B subtype in 143 (in 37.73%), luminal A subtype in 139 (in 36.67%), TNBC in 65 (in 17.15%), and HER2 (+) in 32 patients (in 8.44% of the cases) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Macari et al reported that breast carcinoma occurs at an earlier age in Mexican women compared to women in the USA. Hormone-positive tumors were found to be more prevalent in older patients, while high-grade tumors were more frequently identified in younger patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The numbers roughly reflect the commonality of the cancer types, apart from common cancers like colorectal cancer and skin cancer including melanoma, about which few papers were published. In terms of the topics, our journal publishes articles that highlight racial and ethnic diversity [4,[20][21][22][23][24][25][26][27][28][29] as we mentioned previously [30]. In addition, we have noticed that there has been a huge increase in cancer immunology and immunotherapy interest.…”
Section: Types Of Cancer and Research Covered In World Journal Of Onc...mentioning
confidence: 92%